Handmade Batik Design With Inspiration Story Creation Of Pacitan Eclectic Dance - Kusumaningtyas, Wahyu Rahmadina (Corak, 2022)
Pacitan has various types of arts that are thick with regional elements because almost all regions in Pacitan have exceptional skills following the people's lives in each area. Art is a matter of pride and becomes a regional identity because it is considered crucial in the community. Related to folk art which is a tradition, in Pelem Village, Pringkuku District, Pacitan Regency, East Java, there is a folk art called Eklek Dance. Art is a precious asset because it is the only art owned by the people of Pelem Village. Besides that, it is also because this art presentation is considered very interesting. The background of the design of the written batik with the inspiration of Eklek Dance aims to develop motifs through cultural visuals that still need to be discovered by the public and boost culture and tourism in Pacitan. The approach method used is the method of creating craft art according to Gustami, which includes three stages, namely the exploration stage (extracting the source of ideas, collecting reference sources, to obtain solution materials in design, the design stage (visualization of ideas in the form of verbal descriptions with several considerations from various aspects including material aspects, engineering aspects, aesthetic aspects, and functional aspects. Furthermore, it is continued in the form of 6 alternative sketches) and the embodiment stage (realizing three alternative sketches into the form of works). The results of designing batik motifs with the source of the idea of Pacitan Eklek Dance using primissima cotton material, consisting of 3 design visualizations. The colours used are classic batik colours.